Taxonomic history and review of the Förster genera of Platygastridae (Hymenoptera: Platygastroidea) - Awad, Jessica; Krogmann, Lars; Talamas, Elijah (European Journal of Taxonomy, 2023)
Platygastridae is a ʻdark taxonʼ, with many genera and species in dire need of professional attention. The taxonomic impediment is especially severe in the Palearctic Platygastrinae due to the abundance of names with vague concepts. Historical descriptions and their associated type material must be examined and clarified before further revisionary work can occur. Arnold Förster described 18 genera of Platygastridae, most of which represent distinct and recognizable lineages. The present study reviews their taxonomic history, providing diagnostic remarks, English translations, and illustrations of important specimens from the Förster collection in the Natural History Museum Vienna. The collection also includes original exemplar specimens of European species whose types have been lost. Neotypes and lectotypes are designated from this material to improve nomenclatural stability in the group. Neotypes are designated for Amblyaspis forticornis (Nees, 1834), Isocybus grandis (Nees, 1834), Platygaster striolata Nees, 1834, and Trichacis tristis (Nees, 1834). Lectotypes are designated for Leptacis spinigera (Nees, 1834) comb. nov. and for Platygaster corvina Förster, 1861, with Platygaster henkvlugi Buhl, 1996 treated as a junior synonym. Platygaster mutica Nees, 1834 stat. rev., nomen dubium, is transferred from Synopeas.